Retroaortic left renal vein in open thoracoabdominal aneurysm repair: A modified approach. (7th September 2022) - Idhrees, Mohammed; Velayudhan, Bashi
Abstract: The incidence of retroaortic left renal vein (RLRV) is less than 6%. This anatomical variation hinders the exposure and anastomosis of visceral arteries during open thoracoabdominal aneurysm repair. This situation may warrant division and ligation of the RLRV using the conventional retroperitoneal approach. This report describes a modified approach wherein the vein is not divided, thereby improving its surgical exposure. Abstract : A 24-year-old woman presented with chronic type B aortic dissection (Crawford extent II), extending from aortic arch zone 2 to the aortic bifurcation.